The Association Between Skin Types and Acne Vulgaris - Tamba, Asnita Bella Putri; Jusuf, Nelva Karmila (Talenta Publisher, 2020)
The skin problem often found on adolescents is acne vulgaris. The pathogenesis of acne vulgaris is multifactorial, from increased production of sebum, hyperproliferation of pilosebaceous follicles, colonization of Cutibacterium acnes, to inflammation process. The elevated sebum production which is often linked to oily skin type could result in acne vulgaris in adolescents. According to Baumann Skin Type, one of the parameters in categorizing skin type is having either oily or dry skin. Acne vulgaris is also found on dry skin. This research aims to find the association between skin types and acne vulgaris. It is an analitic research with cross-sectional method. The data were acquired from 93 students of SMA Santo Thomas 1 Medan who fulfilled the inclusion criteria with stratified random sampling method. The collection of data were primarily carried out with dermatology examination and Baumann Skin Type questionnaire to determine the skin types. Then, they were analyzed with Chi-square test to see the relationship between skin types and acne vulgaris. The obtained results show that 73 (78,5%) out of 93 students suffered from acne vulgaris with predominance being female (39,8%) than male (38,7%), and those in 15-year age group (38,7%). The most commonly observed skin type on samples is oily skin (79,6%). The bivariate analysis with acquired p-value of 0,002 (p<0,05) led to a conclusion that there is a significant association between skin types and acne vulgaris.